Islamic Civilization in Europe (Andalusia) from 711 CE to 1492 CE: Peradaban Islam di Eropa (Andalusia) dari 711 M hingga 1492 M - Andi, Nur Fadilah; Hasrawati; Umar Sulaiman (International Journal of Islamic Studies, 2025)
This article discusses the history of Islamic civilization in Europe or Andalusia during the period from 711 CE to 1492 CE. The type of research employed in this study is library research, which focuses on examining literature as the object of study, using books as its data source. The data for this research is obtained from secondary sources, derived from previous studies, involving reading, reviewing, and analyzing various literature relevant to the research. The research findings indicate that the arrival of Islam had a positive impact, enriching life in Andalusia and transforming the region into one of the world's centers of civilization, comparable to the glory of the Umayyad Dynasty in Damascus and the Abbasid Dynasty in Baghdad. Islamic contributions played a crucial role in the development of Western civilization, particularly in the fields of politics, economy, science and technology, astronomy, philosophy, medicine, literature, history, and geography. However, despite the efforts of the Islamic community to maintain its dominance over the centuries, it faced severe challenges such as intra-Muslim conflicts, conflicts with Christians, the absence of a unifying ideology, economic difficulties, and unclear power transition systems. Consequently, Islam eventually relinquished its authority, marking the end of Islamic rule in Spain. Thus, the history of Islam in Andalusia, despite its eventual defeat, reveals Islam as a cultural force that gave rise to various branches of culture in all its diversity and forms. Keywords: European History, Andalusia, Islam